The Development of Building Information Modeling (BIM) with 3D Laser Scanner for Rong Kueak Shrine Conservation: A Case Study of Flood Impact Assessment - Chanthasaen, Parichart; Panbamrungkij, Thitirat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This research focused on the development of Building Information Modeling (BIM) with a 3D laser scanner for the conservation of Rong Kueak Shrine, focusing on a flood impact assessment case study: The Rong Kueak Shrine, situated in Talat Noi, Samphanthawong District, Bangkok that had been experiencing deterioration exacerbated by recurrent flooding. Thus, a BIM model was created by acquiring data through 3D laser scanning, which produced a highly accurate 3D point cloud, with a precision level of 2.9 mm. The data collected were subsequently utilized to construct a BIM model with a Level of Detail (LOD) of 200. Analysis was conducted in conjunction with Digital Elevation Model (DEM) data and flood data provided by the Bangkok Metropolitan Drainage Department, simulating flood levels of 0.1, 0.3, 0.5, 0.8, and 0.5 m., referencing the lowest elevation benchmarks within the study area to estimate potential damages. The assessment evaluated the extent of damage sustained by Rong Kueak Shrine to estimate the associated repair costs. Results revealed that at a flood level of 0.1 m, the damaged area encompassed 197.79 sq.m. At 0.3 m., the damage expanded to 477.43 sq.m. For flood levels of 0.5, 0.8, and 1 m., the damage affected totaling approximately 987.33 sq.m. The estimated damage cost at 0.1 m. was 44,502.75 THB, increasing by approximately 41.43 % and 832.58 % at 0.3 and 0.5 m., respectively. The damage cost remained constant until the 0.8 m. level and increased by approximately 902.78 % at the 1 m. level due to the added cost of electrical system repairs. The calculated damage costs can be used to plan improvements, construction, or repairs by responsible authorities or related parties. Additionally, this information supports the development of preventive measures and strategies for the enhanced conservation of the heritage site.